THE ROLE OF REGIONAL CULTURAL HERITAGE IN SOCIO-CULTURAL DEVELOPMENT AND THE DESIGN OF CITIES AND TOURIST SITES OF THE STAVROPOL REGION (ON MATERIALS OF CAUCASIAN MINERAL WATERS) - Alexandr Kudryavtsev; Evgenii Kudryavtsev (Гуманитарные и юридические исследования)
Since the beginning of the nineteenth century Caucasian Mineral Waters developed as a special historical, cultural, therapeutic territory of Russia, where appearance, sociocultural development and design of the most important cities, was closely linked to their therapeutic functions of balneological health resorts of national and world significance. Based on Russian fortresses and Cossack villages located by the springs, the cities, especially Pyatigorsk and Kislovodsk, were formed not only as spa resorts and unique health centers, but also as large objects of social and cultural purpose. Architectural and structural design of the most significant objects of cultural heritage of Pyatigorsk and Kislovodsk, made in the XIX - early XX centuries by well-known architects of that time, defined the architectural and artistic image of their historic centres. The authors give a general historical overview of the formation of a special sociocultural space of the cities of the Caucasian resorts, the dependence of this process on the macrohistorical context is shown, which reflects how the face and city life changed at critical moments in Russian history.